Adjustment and usage of the irrigameter for management of irriagtion water - Tagliaferre, Cristiano; Santos, Lucas Da Costa [UNESP]; Santos Neto, Izaulto José.; Dos Santos, Tiago Jardim; Rocha, Felizardo Adenilson; Silva, Cláudia santos (Brazilian Journal of Irrigation and Drainage - IRRIGA, 2014)
This study aimed to determine heights of water levels in the evaporimeter of the Irrigameter to directly obtain the evapotranspiration of the crop (ETc) in several stages of its growth. Moreover, evaluate the performance of the Irrigameter at managing irrigation in the bean cowpea crop. The study was conducted in the Campus of the State University of Southwestern Bahia (UESB) in the city of Vitória da Conquista-BA. For the first objective of the study, a completely randomized design with 6 treatments and 3 replications was used, in which the Irrigameters ran with different levels of water inside the evaporimeter. The second objective was related to evaluation of the Irrigameter technology as opposed to other methodologies for managing irrigation in bean cowpea crop. The use of different levels of water in the evaporimeter of the Irrigameter makes it possible to directly estimate the evapotranspiration of the crop in its different stages of growth. Among the study methods, the Class A tank was the only one which was statistically different from the standard method of greenhouse. The irrigameter had a good performance in directly estimating the levels of irrigation.
Ajuste e aplicação do irrigâmetro no manejo da água de irrigação
Keywords: Evapotranspiration; Management of irrigation; Soil moisture